Adipositas und körperliche Aktivität bei Erwachsenen = Obesity and physical activity in adults - Wirth, Alfred (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Increased physical activity is of major importance for prevention and therapy of obesity. The database for prevention is insufficient, exercise is probably of major importance. Reduction of body weight, body fat, and visceral fat is best achieved by endurance exercise at moderate and high intensity. Resistance training reduces body weight and body fat minimal but preserves muscle mass following an intensive training programme. For weight loss a combination of endurance and resistance training is most effective. Following diet-induced weight loss a comprehensive training programme is necessary to prevent weight regain. Beside changes on body weight and body composition increased physical activity has positive effects on risk factors, diseases and quality of life.
Gesehen am 18.10.2019